THE APPLICATION OF NN TO MANAGEMENT PROBLEMS - Coelho, Arnaldo; Moutinho, Luiz; Hutcheson, Graeme D; Santos Silva, Maria Manuela (Quantitative Modelling In Marketing And Management, 2012)
This chapter attempts to make available to the reader the main insights into the world of artificial neural networks (ANNs), seen as a generalized mathematical models which emulate human cognition, as well as, highlights several contributions of this statistical methodology trained by the multiple backpropagation algorithm in the management field. Artificial neural networks are pattern recognition algorithms capable of capturing salient features from a set of inputs and map them to outputs without making a priori assumptions about the specific nature of the relationships. It was shown that ANN modelling demonstrates good capacity to provide additional explanations to the different investigation problems, namely, giving the opportunity to identify new and different linkages between the variables in the models. At the same time, this modelling can be faced as a new departure in the search of new solutions, giving insights to the use of other modelling tools, like SEM and others, which have a more confirmatory naure.